Effects of Three Dimensions of Shared Leadership on Team Members’ Perceptions on Trust and Team Performance - Mirim Kim; Soo Jeoung Han (Adult Education Research Conference, 2019)
We conducted a survey with teams to identify the underlying dimensions of shared leadership and examine the effects of shared leadership on the level of trust and team performance.
Keywords: three dimensions of shared leadership; team trust; team performance